Use of a formula to assess patient satisfaction and expectations through neuro-linguistic programming - Marco Tulio Rodrigues da Cunha; Danilo Uhlemann (Revista Brasileira de Cirurgia Plástica, 2018)
Introduction: A major concern of patients who are candidates for a plastic surgery is failure to achieve expected results. Neurolinguistic programming (NLP) provides an understanding of the structure of language, clues about how people think, and how these patterns of thought affect behavior. The objective of this study was to validate the use of a formula based on NLP to assess patient satisfaction and expectations. Methods: NLP techniques were employed to improve communication and assess patient expectations. Using NLP, the average number of surgeries performed in the past 5 years and the reappraisal index were compared with those in the previous 5 years, in which the methods described in this article were not employed. Results: The average annual growth rate in the previous 5 years was 5% and the average rate verified after introduction of NLP methodology increased to 10%; the reappraisal and additional surgery index decreased from 20% to 10% in the same period. Conclusions: The use of NLP helped us to understand patient expectations in a more consistent manner for the periods analyzed, significantly increasing the number of operated patients and reducing the rate of reappraisal and additional surgeries.